Pemerintahan Daerah dalam Meningkatkan Kualitas Pelayanan Ijin Mendirikan Bangunan (IMB) - Pranata, Yudicia (Jurnal Administrasi Publik, 2013)
By the presence of  regional autonomy and  also by the presence of Act No. 32 of 2004 as amended by Act No. 12 of 2008 About local governance, bureaucracy at the expected can provide services as maximum as possible according to the wants and needs of society, no exception  in bureaucratic licensing, especially a building permit ( IMB ). The problem that often arises at the time the building permit process (IMB) is about a process that is reasonably slow, tend to be convoluted and the rise of the practice of the extortion. This indicates that services public that is performed bureaucrats so far not been shown progress toward better quite the contraryThe research method used was qualitative research with a descriptive approach.KPPT performance in improving the quality of service the building Permit (IMB) already can be said to be good, it can be seen from the apparatus competency of service providers (HR), facilities and infrastructure, a mechanism consisting of the procedure of service, time of completion of the service, and the cost of service, accompanied by the attainment of performance targets, objectives, vision and mission of the organization. The quality of service at KPPT Batu city, basically good and already has achieved what quality services. Said so,in line with expectations and satisfaction of the public as service users   Keywords : Performance, Local Government, Quality, Service, Building Permit (IMB).